The mythical pursuit of happiness - a mirage of happiness : a brief overview of the philosophy of happiness - Rupčić Kelam, Darija (Array, 2020)
According to some authors, there are several significant projects on the human agenda in the twenty-first century. One of them is the pursuit to find the key to personal happiness. Increasingly, people are beginning to see that systems once created to strengthen a nation, such as the education, the health system, and the welfare system, should serve the happiness and well-being of the individual, not the other way around. Thus, the right to the pursuit of happiness has been transformed into a natural right to happiness. Harari argues that GDP per capita, as a primary measure of national performance assessment, should be supplemented or replaced by GDH – gross domestic happiness. In this paper, we will examine some of the dominant ideologies and strategies aimed at achieving this goal. Optimization of human experience, self deception strategies, and the doctrine of harmony all serve as filters of the reality of the individual. It is necessary to deceive people, to bring them into the state of cheerfulness, to become a cheaper, more productive, and optimal worker in service of capital. The very idea of achieving social harmony is a control mechanism aimed at maintaining balance within the corporate community. Nevertheless, what lies behind the tyranny of unity and the pursuit of happiness is turning into a life that conceals reality and leads to a more profound and further depletion of the range of social, emotional, and personal relationships. Can recognizing a wide range of human emotions, as well as the essential determinants of a human being, such as caring and empathy, help us to live an authentic and happier life?